PENGARUH PEMONITORAN EKSTERNAL TERHADAP SENSITIVITAS KOMPENSASI - KINERJA - NUR FADJRIH ASYIK; KHOMSIYAH KHOMSIYAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
This study examines the effect of external monitoring on the compensation performance sensitivity. We use two proxies for performance, are accounting performance (ROA) and market performance (stock price). Based on agency theory, we predict that external monitoring (regulation, bank loan, blokholder, and growth opportunity) increase the compensation-performance sensitivity. Using 74 observation, the result demonstrates that neither accounting nor market performance has a significant effect on compensation. We found significant effect of external monitoring on the compensation performance sensitivity. Overall, the results indicate there are the higher sensitivity of compensation performance by inclusion the external monitoring than compesation performance per se.